Religious Values in the Cenk Blonk Shadow Puppet Show - Ni Ketut Dewi Yulianti; I Wayan Suardana; Wardizal Wardizal; Ni Wayan Ardini; I Komang Darmayuda; Ni Kadek Dwiyani; Agus Darma Yoga Pratama (Jurnal Penelitian Agama Hindu, 2026)
The transformation of traditional performing arts in the digital era has opened new possibilities for transmitting religious values and moral education to younger generations who are increasingly influenced by media-driven cultural change. In this context, the Cenk Blonk shadow puppet show represents a contemporary adaptation of Balinese wayang kulit that combines humor, social criticism, and spiritual reflection, while remaining rooted in Hindu-Balinese ethical teachings. This study aims to analyze the representation of religious values and moral messages in three Cenk Blonk shadow puppet performances uploaded on YouTube, namely Backing Sakti, Tidak Cukup Hanya Cinta, and Sebuah Renungan (Setan dalam Diri). This research employs a descriptive qualitative approach using qualitative content analysis of narrative structures, dialogues, and symbolic expressions, reinforced by semi-structured interviews with the puppeteer to strengthen contextual interpretation. The findings reveal that the performances consistently articulate key religious values, including honesty (satya), self-control (dama), tolerance, compassion, and non-violence (ahiṁsā). These values are conveyed through character contrasts, humorous satire, and symbolic conflicts that reflect contemporary socio-political, familial, and religious realities. Moral messages emphasize ethical leadership, household harmony, religious humility, and interfaith respect, presented in ways that encourage reflection rather than didactic instruction. The study concludes that Cenk Blonk performances function as an effective culture-based educational medium that integrates entertainment and moral reflection. Through digital dissemination on YouTube, these performances expand their pedagogical reach and demonstrate the relevance of traditional arts in strengthening contextual, inclusive, and humanistic character development in the digital era.